2019
DOI: 10.1021/acsearthspacechem.9b00147
|View full text |Cite
|
Sign up to set email alerts
|

Plutonium Retention Mechanisms by Magnetite under Anoxic Conditions: Entrapment versus Sorption

Abstract: The reliable prediction of possible plutonium migration into the geological environment is crucial for the safety assessment of radioactive waste repositories. Fe­(II)-bearing corrosion products like magnetite, which form on the surface of steel waste containers, can effectively contribute to the retardation of the potential radionuclide release by sorption and redox reactions, eventually followed by formation of secondary precipitates. A retardation process even more efficientespecially when considering the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 81 publications
1
10
0
Order By: Relevance
“…However, studies suggest the U­(IV) forms a binuclear complex on magnetite at defect or lattice step/kink sites, which is distinct from the tetradentate Pu­(IV) adsorption species observed in this study. A recent study also observed partial incorporation of Pu as Pu­(III) following coprecipitation with magnetite. Here the Pu had a split Pu–O shell with four O scatterers at 2.22 and 2.45 Å attributed to a pyrochlore-like coordination environment within the structure.…”
Section: Plutonium Sorption During Ferrihydrite Formation and Crystal...mentioning
confidence: 99%
“…However, studies suggest the U­(IV) forms a binuclear complex on magnetite at defect or lattice step/kink sites, which is distinct from the tetradentate Pu­(IV) adsorption species observed in this study. A recent study also observed partial incorporation of Pu as Pu­(III) following coprecipitation with magnetite. Here the Pu had a split Pu–O shell with four O scatterers at 2.22 and 2.45 Å attributed to a pyrochlore-like coordination environment within the structure.…”
Section: Plutonium Sorption During Ferrihydrite Formation and Crystal...mentioning
confidence: 99%
“…15 Both the sorption/desorption of Pu to mineral colloid surfaces (pseudocolloids) and formation of Pu oxide colloids (intrinsic colloids) associated with mineral surfaces, as well as Pu coprecipitation with secondary minerals are all likely important environmental processes under a range of geochemical conditions. 11,14,22,57,58 For example, in groundwater at the Mayak site (Russia), colloidal amorphous iron oxides with associated Pu were found up to 4 km away from the contamination source. 59 In contaminated soils at Los Alamos National Laboratory, Batuk et al 60 identified unusual Pu−Fe particles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…At high Pu concentrations (>10 –8 M), Pu­(IV) intrinsic colloids have been shown to form on the surface of various oxide minerals including iron oxy­(hydroxide) minerals. ,,, On the goethite surface, Pu­(IV) colloids may undergo a lattice distortion, because of epitaxial growth, which leads to a stronger surface binding compared to other mineral phases, such as quartz . Both the sorption/desorption of Pu to mineral colloid surfaces (pseudocolloids) and formation of Pu oxide colloids (intrinsic colloids) associated with mineral surfaces, as well as Pu coprecipitation with secondary minerals are all likely important environmental processes under a range of geochemical conditions. ,,,, For example, in groundwater at the Mayak site (Russia), colloidal amorphous iron oxides with associated Pu were found up to 4 km away from the contamination source . In contaminated soils at Los Alamos National Laboratory, Batuk et al .…”
Section: Introductionmentioning
confidence: 99%
“…With similar spectroscopic tools, Bargar et al described how biogeochemical processes can tune the uranium speciation within domains that are of the order of a few nm. [42,43] At a much larger spatial scale (few cm), the implementation in situ of DGT (Diffusive Gradient in Thin film) and DET (Diffusive Equilibrium in Thin film) in wetlands impacted by former mining activities in the French Massif Central region provides a vertical mapping of Nat U gradient. The depth profiles with fairly good spatial resolution (a few cm) show the correlation with the soil nature, the organic content matter, all factors combined with the history of the site.…”
Section: Speciation In Field Studies [Dealing With Spatial Heterogene...mentioning
confidence: 99%